The effect of surface treatment of polymethyl methacrylate denture base on the soft-liner bond strength - Fernandy Hartono Prasetyo; Muslita Indrasari (Indonesian Journal of Prosthodontic, 2023)
The increased use of removable denture in elderly population are followed by the increased use of soft liner for denture reline due to bone resorption. However, soft liners are found to be bonded poorly to polymethyl methacrylate (PMMA) denture base. Thus, several methods are developed in order to improve the bonds between denture base and soft liner, i.e., mechanical methods (sandblast, sandpaper, laser), chemical methods (MMA monomer, acids, acetone, and plasma), or combination of both. This article evaluates the effectiveness of various surface treatment methods of PMMA materials in improving the bonds with silicone or acrylic-based soft liner. It is concluded that surface treat-ment on the PMMA in general increase the bond strength with the soft liners compared to the control group; the use of Er:YAG laser and MMA monomer show the highest bond strength between the PMMA and soft liner materials. Several factors such as the duration of treatment and the laser intensity energy may affect the bond strength bet-ween PMMA and soft liner. Acrylic-based soft liner in general shows better bond strength than silicone-based soft liner, nevertheless both materials show improvement in bond strength with PMMA after surface treatments.